Parental Containing Function and Overprotection in Specific Learning Disorder - Koyuncu, Zehra; Zabcı, Neslihan; Durcan, Gizem; Doğangün, Burak (Cerrahpaşa Medical Journal, 2022)
Objective: This study aimed to evaluate the relationship between maternal containment and overprotectiveness in children with specific learning disorder and also planned to evaluate the level of autonomy in self-care skills, which may be disrupted by overprotection. Methods: In total, 56 children with specific learning disorder diagnosis were compared with 56 healthy controls. Schedule for Affective Disorders and Schizophrenia for School-Age Children Present and Lifetime Version-DSM-5, Wechsler Intelligence Scale for Children-Revised, Mathematics, Reading, Writing Assessment Scale, Parental Child Containing Function Scale, and overprotection subscale of Parent Attitude Scale were used as assessment tools. Results: Parental Child Containing Function Scale and Parent Attitude Scale -overprotection scores were significantly higher in children with specific learning disorder (P < .001 for both). Furthermore, Parent Attitude Scale-overprotection have a predictive role in specific learning disorder diagnosis (odds ratio = −0.879, 95% CI = −0.788 to −0.980, P = .020). Also, some Parental Child Containing Function Scale (PCCFS) subscales were found as predictors of Mathematics, Reading, and Writing Assessment Scale scores. Lastly, children with specific learning disorder diagnoses were less autonomous in their self-care abilities. Conclusion: In this study, parenting functions and attitudes were investigated in specific learning disorder for the first time. Lower containing function and overprotectiveness were found to be associated with specific learning disorder and also to have determinant roles for learning problems. In addition, it was thought that children with specific learning disorder might need supportive parental attitudes in order to develop their autonomy in their self-care. Cite this article as: Koyuncu Z, Zabcı N, Durcan G, Doğangün B. Parental containing function and overprotection in specific learning disorder. Cerrahpaşa Med J. 2023;47(1):81-87.